Photoacoustic imaging and photothermal therapy in the second near-infrared window. (17th May 2019) - Ge, Xiaoguang; Fu, Qinrui; Bai, Lin; Chen, Bin; Wang, Renjie; Gao, Shi; Song, Jibin
Abstract : This review summarizes the recent progress of PA imaging and PTT agents in the second NIR window. Abstract : The second near-infrared (NIR-II) window, with a broadband absorption ranging from 1000 nm to 1350 nm, has received increasing attention for photoacoustic imaging and imaging-guided NIR-II photothermal therapy. Compared to conventional nanoagents in the first near-infrared (NIR-I) window, with an optical absorption of 700–1000 nm, NIR-II nanoagents offer various merits such as high-performance photothermal treatment outcomes and photoacoustic imaging with both deeper tissue penetration and higher SNR. Thus, this review focuses on the recent progress in photoacoustic imaging and photothermal therapy in the NIR-II window. The merits of the NIR-II window relative to the NIR-I window are systematically compared. This is followed by a summary of nanoagents in the NIR-II window and their biomedical application, including photoacoustic imaging in the NIR-II window and imaging-guided NIR-II photothermal therapy. Finally, the prospects and challenges of both photoacoustic imaging and photothermal therapy in the NIR-II window are summarized.